Advances and prospects in biomimetic multilayered scaffolds for articular cartilage regeneration. Issue 6 (30th September 2020) - Fu, Liwei; Yang, Zhen; Gao, Cangjian; Li, Hao; Yuan, Zhiguo; Wang, Fuxin; Sui, Xiang; Liu, Shuyun; Guo, Quanyi
Abstract: Due to the sophisticated hierarchical structure and limited reparability of articular cartilage (AC), the ideal regeneration of AC defects has been a major challenge in the field of regenerative medicine. As defects progress, they often extend from the cartilage layer to the subchondral bone and ultimately lead to osteoarthritis. Tissue engineering techniques bring new hope for AC regeneration. To meet the regenerative requirements of the heterogeneous and layered structure of native AC tissue, a substantial number of multilayered biomimetic scaffolds have been studied. Ideal multilayered scaffolds should generate zone-specific functional tissue similar to native AC tissue. This review focuses on the current status of multilayered scaffolds developed for AC defect repair, including design strategies based on the degree of defect severity and the zone-specific characteristics of AC tissue, the selection and composition of biomaterials, and techniques for design and manufacturing. The challenges and future perspectives of biomimetic multilayered scaffold strategies for AC regeneration are also discussed.